THE ANALYSIS STUDY OF DIAGNOSIS AND MANAGEMENT OF CONTACT DERMATITIS: A SYSTEMATIC REVIEW OF RANDOMIZED CONTROLLED TRIALS AND PRIMARY STUDIES - Prety Pranitacitra; Ayu Dwi Mutia (International Medical Journal Corp. Ltd, 2026)
Introduction: Contact dermatitis (CD) encompasses allergic contact dermatitis (ACD), irritant contact dermatitis (ICD), and occupational variants, representing the most prevalent occupational dermatosis globally. Despite substantial disease burden, diagnostic accuracy remains inconsistent and therapeutic strategies vary widely across clinical settings. This systematic review comprehensively evaluates current evidence regarding diagnostic modalities and therapeutic interventions for CD. Methods: The study strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines (2003–2026). Inclusion criteria encompassed randomized controlled trials and primary studies assessing CD diagnosis or treatment in human subjects. Risk of bias assessment utilized Cochrane RoB 2.0 and Newcastle-Ottawa Scale. Results: Patch testing confirmed ACD in 50–87.5% of clinically suspected cases, yet utilization rates remained below 7.4% in insured populations. Nickel sulfate, fragrance mixes, and methylisothiazolinone constituted predominant allergens. Topical corticosteroids and calcineurin inhibitors demonstrated significant efficacy as first-line therapies. Dupilumab achieved Hand/Foot IGA 0/1 in 40.3% versus 16.7% placebo (P=0.003). Lipid-rich barrier preparations effectively prevented and treated ICD. Systemic agents including cyclosporine and JAK inhibitors showed improvement in refractory disease. Discussion: CD requires individualized diagnostic-therapeutic approaches integrating patch testing, allergen avoidance, barrier restoration, and targeted anti-inflammatory therapy. Significant barriers—sociodemographic, geographic, and systemic—limit diagnostic access. Novel biologics represent a paradigm shift for recalcitrant disease. Conclusion: Multimodal CD management incorporating accurate diagnosis, allergen avoidance, and appropriate pharmacotherapy achieves optimal outcomes. Future CD-specific RCTs and improved patch testing access are research priorities.